Retraction Note: CYPA promotes the progression and metastasis of serous ovarian cancer (SOC) in vitro and in vivo - Zhi-Ying Qi; Fang Wang; Ying-Ying Yue; Xue-Wang Guo; Rui-Meng Guo; Hong-Lin Li; Yan-Ying Xu (Journal of Ovarian Research, 2023)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s13048-019-0593-2.